Thermoelectric properties of novelmicrostructurally modifiedcosb3skutterudite materials by minor dopants of Mn, Hf, Al, Bi and Yb / Mohamed Hamid Elsheikh Yousef - Mohamed Hamid , Elsheikh Yousef (2016)

(untitled)
A key challenge in thermoelectrics research is obtaining materials with high electrical conductivity, a high Seebeck coefficient and low thermal conductivity. The essence of the phonon-glass electron-crystal (PGEC) concept is to synthesize ultimate thermoelectric materials that can conduct electricity like a crystal but insulate heat like a glass. In this respect, the skutterudite system is a promising material that utilizes the PGEC concept. The skutterudite system relies on a crystal “cage-like” structure with a rattler atom to allow simultaneous high electrical conductivity and low thermal conductivity. In this work, the skutterudite compound was modified by adding Mn, Hf and Alx (x = 0.3, 0.6 and 2) to the binary skutterudite CoSb3 and Alx (x = 0.1, 0.2 and 0.3), Bi0.1 and Al0.1Bi0.05 to the ternary skutterudite Yb0.25Co4Sb12. The fabrication method utilized the mechanical alloying (MA) technique followed by the spark plasma sintering (SPS) process. The addition of Mn, Hf, and Alx to the binary skutterudite CoSb3 resulted in the formation of a polycrystalline skutterudite phase with Mn, Hf, and Al located in the grain boundaries. Moreover, the addition of Mn and Al led to an increase in the area fraction of the grain boundary compared with the addition of Hf, leading to an overall modification of the skutterudite microstructure. The addition of Mn, Hf, and Al had a significant effect on the lattice thermal conductivity of CoSb3, which was reduced by up to ~60% by the addition of Hf. However, the tradeoff for the microstructural modification of binary skutterudite is the relatively high electrical resistivity, thus resulting in moderate figures of merit (ZTs < 0.1). Therefore, grain boundary modification is an effective strategy to decrease thermal conductivity for this case. iv A similar strategy for microstructural modification to introduce element-rich boundary regions was demonstrated to be effective for the addition of Alx, Bi0.1 and Al0.1Bi0.05 to Yb0.25Co4Sb12 ternary skutterudite. Al- and Bi-rich regions were found to exist at the nano-scale along the grain boundaries. An overall improvement in all three parameters was found in comparison to undoped CoSb3. A figure of merit ZT value of more than unity (ZT = 1.36) was found using this strategy. Thus, this work is useful in deriving a pathway for improvement in thermoelectrics through microstructural modification. An introductory investigation of n- to p-type inversion of the skutterudite thermoelectric material was demonstrated through the formulation of bulk skutterudite Al0.3Co4Sb12. A wide range of Seebeck coefficient values from -251 μV/K at low temperature to +153 μV/K at high temperature with a critical point at 200 °C is reported. This formulation serves as the starting point for new fundamental investigations of the p- to n-type inversion phenomena in thermoelectrics. In addition, this finding indicates the potential of this material as a temperature switch.